Penerapan Active Cycle of Breathing Technique untuk Mengatasi Masalah Bersihan Jalan Nafas pada Pasien Tuberkulosis Paru dengan Bronkiektasis: Studi Kasus - Vika Endria; Sri Yona; Agung Waluyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to identify the effectiveness of the Active Cycle Breathing technique (ACT) nursing intervention in overcoming the problem of an ineffective airway through a series of respiratory control, deep breathing and sputum expulsion techniques. The method used is a single case study. Respondents of this study were patients with active pulmonary tuberculosis with broad lesions with bronchiectasis. The results showed that after being given ACT intervention for seven days, there was an increase in oxygenation status, a decrease in sputum, and shortness of breath. In conclusion, ACT intervention is effective in reducing airway clearance problems. Keywords: TB Bronchiectasis, Cycle Breathing Technique, Breathing Exercises, Wide Lesion TB, Pulmonary TB